STATE OF ORAL HYGIENE IN 7-12-YEAR-OLD SCHOOLCHILDREN WITH DIFFERENT DENTAL STATUS - Kaskova, L.F.; Godovanets, O.I.; Mandziuk, T.B.; Kotelban, A.V.; Mytchenok, M.P. (World of Medicine and Biology, 2023)
Caries remains the most common dental disease in children and adolescents, despite the fact that scientists, doctors and other specialists pay attention to its prevention. A special role is given to local factors, among which the state of oral hygiene plays a leading role. The purpose of this research was to study the state of oral hygiene in children aged 7–12 years with different dental status.134 children aged 7–9 years, corresponding to the first period of mixed bite and 84 children aged 10–12 years (second period of mixed bite), were examined. According to WHO recommendations, the oral hygiene status was determined using the GreenVermillion hygiene index (OHI-S), as well as the Fedorov-Volodkina index. The study of oral hygiene in children at different age periods indicates its improper condition, especially in children with carious lesions, which is confirmed by its study using various hygienic indices. With age, the state of hygiene improves in children without caries, while it worsens in children with caries. The obtained data indicate the need to carry out preventive work with children and, especially with those who have caries, regarding hygienic education, care of the oral cavity, the use of basic and auxiliary objects and means of oral hygiene, which will permit to create conditions for healthy formation and functioning of teeth hard tissues.